2008
DOI: 10.4103/0019-5154.41651
|View full text |Cite
|
Sign up to set email alerts
|

A study on the etiological agent and clinico-mycological correlation of fingernail onychomycosis in eastern India

Abstract: Background:Onychomycosis manifests itself in various forms, notably onychodystrophy, onycholysis, subungual hyperkeratosis, or nail-plate discoloration. Not necessarily nail changes mentioned here should always be of fungal origin.Objective:The present study is planned to get an idea about etiological agent and clinical correlation in fingernail onychomycosis.Materials and Methods:Nail-clipping and subungual debris of patients with above mentioned nail changes were subjected to KOH preparation. Culture was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 11 publications
7
24
1
Order By: Relevance
“…In studies which were conducted by Lone et al in Kashmir, Aghamirian et al in Iran, Kaur et al in New Delhi, Das et al in Kolkata and Jesudanam et al in Vishakhapatnam, 60%, 40.2%, 54.5%, 51.76% and 45.53% samples respectively were found to be positive by direct examination and/or culture. 9,14,[16][17][18] In our study, culture positivity (79%) was more than microscopy (63%), similar to another study conducted by Das et al in 2008 in Kolkata, where 32.9% were positive by direct microscopy and 49.4% by culture. While, studies conducted by Lone et al in 2013 and Shenoy et al in 2008 found more positivity by direct microscopy than culture, with a positive result by microscopy in 56% and 53% and culture positivity in 40% and 35% respectively.…”
Section: Discussionsupporting
confidence: 78%
“…In studies which were conducted by Lone et al in Kashmir, Aghamirian et al in Iran, Kaur et al in New Delhi, Das et al in Kolkata and Jesudanam et al in Vishakhapatnam, 60%, 40.2%, 54.5%, 51.76% and 45.53% samples respectively were found to be positive by direct examination and/or culture. 9,14,[16][17][18] In our study, culture positivity (79%) was more than microscopy (63%), similar to another study conducted by Das et al in 2008 in Kolkata, where 32.9% were positive by direct microscopy and 49.4% by culture. While, studies conducted by Lone et al in 2013 and Shenoy et al in 2008 found more positivity by direct microscopy than culture, with a positive result by microscopy in 56% and 53% and culture positivity in 40% and 35% respectively.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, 20% samples were identified as false negative (KOH negative and culture positive). False negative findings had also been observed in previous reports [5,7,14].…”
Section: Discussionmentioning
confidence: 58%
“…There is a long list of fungi which have a tendency to damage the nail, like dermatophytes (50%), yeasts (27%) and molds (23%) [7]. However, all the nail diseases are not fungal in origin they are also caused by other clinical conditions [6] like trauma, wet work (with the hand submerged in water) [8], HIV-AIDS [6], immunodeficiency which is due to organ or bone marrow transplantation [6], old age, psoriasis, atopic dermatitis [9], diabetes with a predominance of Candida spp [10], renal transplant recipients [11], etc.…”
Section: Introductionmentioning
confidence: 99%
“…19 In our study yeast OM was high at 30.8% followed by DLSO (Distal Lateral Subungual Onychomycosis) and TDO (Total Destructive Onychomycosis) in 20.5% each. In our study we have also included cases which were also positive for yeasts in direct microscopy despite of them being negative in culture.…”
supporting
confidence: 46%
“…Some studies have not found diabetes as co-morbidity in OM. 11,19 In our study also it was not found to be significantly associated with OM when compared to the fungus negative group. On other hand, Onychomycosis has been found to be more common in diabetic patients than in non-diabetics by another study.…”
contrasting
confidence: 44%